Study of change connectedness hemadens of power centers in the states of organism of man (Eurasian Journal of Ecology, 2016)
Endocrine glands – not just a physiological system that provides and is responsible for the secretion of hormones person. Endocrine system and energy centers are very connected. Energy centers connects the human body with special channels and regulates energy metabolism.
Keywords: endocrine glands; chakra; bioenergy field.